2013
DOI: 10.1016/j.neuroimage.2013.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic causal modelling of effective connectivity during perspective taking in a communicative task

Abstract: Previous studies have shown that taking into account another person's perspective to guide decisions is more difficult when their perspective is incongruent from one's own compared to when it is congruent. Here we used dynamic causal modelling (DCM) for functional magnetic resonance imaging (fMRI) to investigate effective connectivity between prefrontal and posterior brain regions in a task that requires participants to take into account another person's perspective in order to guide the selection of an action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Only a limited number of studies to date have examined perspective-taking in a communicative context (Dumontheil et al, 2010; Hillebrandt et al, 2013; Wardlow, 2013; Wardlow et al, 2014). For example, in an fMRI study of healthy volunteers, Dumontheil et al, (2010) used a variant of the director task, originally described by Keysar and colleagues (Keysar et al, 2000, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a limited number of studies to date have examined perspective-taking in a communicative context (Dumontheil et al, 2010; Hillebrandt et al, 2013; Wardlow, 2013; Wardlow et al, 2014). For example, in an fMRI study of healthy volunteers, Dumontheil et al, (2010) used a variant of the director task, originally described by Keysar and colleagues (Keysar et al, 2000, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The authors report activation in mPFC and left temporal pole for the critical condition (director present, 3-objects), which partially overlaps with our findings. In a follow-up study, Hillebrandt et al, (2013) used dynamic causal modeling to show that the social demands of the task modulate backward connections from mPFC. The paradigm in both studies, however, is comprehension-based and requires subjects to identify the target object via a motor response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify and summarise regional responses for further dynamic causal modelling we used standard procedures37. Timeseries from VOIs associated with the above contrasts were summarised using the SPM12b Eigenvariate toolbox: we extracted each participant's principal eigenvariate around the participant-specific local maxima activations nearest to the peak voxel of the group (between subject) GLM analysis (see Table 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…As reasoned above, one possible explanation might be that of a qualitative difference between individuals with and without ASD. For instance, as the processing of socially relevant information might be less efficient in subjects with high autism traits [Frith, ], our observation of increased dmPFC‐pSTS connectivity during mentalizing might reflect a compensatory mechanism in nonclinical groups for enhanced detection and inference of social meaning [Hillebrandt et al, ; Nummenmaa et al, ]. Finally, previous studies in ASD patients have reported altered connectivity of temporal areas with lower level sensory brain regions during animated shapes tasks, such as visual area V3 [Castelli et al, ] and lateral fusiform gyrus [Weisberg et al, ].…”
Section: Discussionmentioning
confidence: 75%